A new front line? Workforce development issues from an evolving fire service. Issue 2 (14th December 2020) - Simcock, Tom
Abstract : Purpose: Over the past twenty years, the Fire and Rescue Services (FRS) workforce in England has experienced significant developments as part of New Labour's modernisation agenda with the Fire and Rescue Services Act 2004 and the increasing focus on prevention and community safety. Subsequent organisational changes and the introduction of new community safety services dynamically altered the role of fire fighters and introduced new roles into these organisations. The purpose of this paper is to explore the issues relating to an evolving fire service workforce and the tensions present in the development of new professional roles. Design/methodology/approach: An exploratory qualitative critical realist case study approach was undertaken, employing semi-structured interviews and focus groups of employees across one FRS in England. Findings: The findings of the present study identify several emerging issues from a changing fire service: in particular, the frictions between different aspects of the organisation and the tensions in the development of career "ladders" for non-operational roles. Originality/value: To the author's knowledge, this is the first paper that examines the issues surrounding the development and evolution of professional roles in community safety aspects within the FRS in England.